Effects of 8-week zumba exercise on blood lipids profile in sedentary women - Mine Turgut; Yusuf Soylu (IP Iermakov S.S., 2021)
Background and Study Aim. Different aerobic exercise may affect women's health behaviours. Therefore, this study aimed to determine the effect of 8-week Zumba exercises applied to sedentary women on lipid profile. Material and Methods. Fifty voluntary healthy sedentary women with a mean age of 32.1 ± 6.8 years and a mean height of 158.4 ± 15.5 cm participated in the study. Before and after the exercise program, blood samples and body weight were taken on before breakfast in the morning by experts in the appropriate laboratory environment, some environmental measurements. In the analysis of the data, the SPSS 22.0 package program was used to compare the pre-post exercise values (Paired Sample T-Test) as well as descriptive statistics. The effect sizes (Cohen's d) were calculated to provide the estimation of the comparisons between the pre-test and post-test results of the obtained values. Results. According to the results, it was determined that there were significant differences between blood lipids Glucose, Urea, Triglyceride, total High-Density Lipoprotein Cholesterol (HDL-C) and Low-Density Lipoprotein Cholesterol (LDL-C) levels before and after Zumba exercise program (p <0.05). In addition, it was determined that there was a significant and positive change between the pre-test and post-test BMI values (p <0.05). Conclusions. According to the results of the study, it was concluded that the 8-week Zumba exercise program applied to sedentary women had a positive effect on the lipid profiles of women.